2020
DOI: 10.1177/0003489420929362
|View full text |Cite|
|
Sign up to set email alerts
|

The Clinical Significance of IGF-1R and Relationship with Epstein–Barr Virus Markers: LMP1 and EBERs in Tunisian Patients with Nasopharyngeal Carcinoma

Abstract: Objectives: Tunisia is in the endemic area of nasopharyngeal carcinoma. Epstein–Barr virus (EBV) based assays have been commonly used as standard markers for screening and monitoring the disease. So, it is very important to find novel factors for the early diagnostic and prognostic evaluation of this cancer. The aim of the study was to evaluate the expression of IGF-1R (Insulin Growth Factor Receptor 1), LMP 1 (Latent Membrane Protein 1) and EBERs (EBV encoded RNAs) in order to determine their correlation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…These data are valuable because identification of early cellular changes in NPC pathogenesis may serve clinicians in early identification for disease and/or in guiding treatment. One study found that higher levels of LMP1 were associated with larger tumor size and poorer 5-year survival [160]. Others have identified EBV DNA, and downstream effects of viral proteins (such as markers of oxidative stress, RIP3 hypermethylation) to be informative prognostic indicators [161].…”
Section: Cellular Mechanisms Of Ebv-mediated Nasopharyngeal Carcinoge...mentioning
confidence: 99%
“…These data are valuable because identification of early cellular changes in NPC pathogenesis may serve clinicians in early identification for disease and/or in guiding treatment. One study found that higher levels of LMP1 were associated with larger tumor size and poorer 5-year survival [160]. Others have identified EBV DNA, and downstream effects of viral proteins (such as markers of oxidative stress, RIP3 hypermethylation) to be informative prognostic indicators [161].…”
Section: Cellular Mechanisms Of Ebv-mediated Nasopharyngeal Carcinoge...mentioning
confidence: 99%
“…Immunohistochemistry identified EBV latent membrane protein 1 using tissue sections in apical and periapical periodontitis lesions (Fig. 5 B) [ 115 , 116 ], in patients with nasopharyngeal carcinoma [ 117 ], in immunocompetent adult [ 118 ], and in Hodgkin's disease and non-Hodgkin's lymphoma [ 119 – 121 ].…”
Section: Immunohistochemical Detection Of Viral Pathogensmentioning
confidence: 99%
“…These data are valuable because identification of early cellular changes in NPC pathogenesis may serve clinicians in early identification for disease and/or in guiding treatment. One study found that higher levels of LMP1 was associated with larger tumor size and poorer 5-year survival [141]. Others have identified EBV DNA, and downstream effects of viral proteins (such as markers of oxidative stress, RIP3 hypermethylation) to be informative prognostic indicators [142].…”
Section: Cellular Mechanisms Of Ebv-mediated Nasopharyngeal Carcinoge...mentioning
confidence: 99%